Composite diaphragm as well as preparation method and application thereof
By adopting a composite coating design in the lithium-ion battery separator and combining the optimized ratio of organic polymers A and B, the problems of insufficient liquid retention capacity and corner lithium in large-scale batteries are solved, and higher electrolyte liquid retention capacity and lower ion transmission resistance are achieved.
Patent Information
- Application Number
- CN202411876008.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
AI Technical Summary
In the large-scale lithium ion battery, the existing oil-based separator has problems of corner lithium-ion corner lithium-ion problems caused by small pore size, limited liquid retention capacity, non-compressibility and non-standard through-hole structure.
A composite separator design is adopted, including a base film and a composite coating coated on one or two sides of the base film. The slurry of the composite coating consists of organic polymer A and organic polymer B, with a specific mass ratio, particle size distribution width and additive ratio to improve adhesion, compressibility and large through-hole structure.
It significantly improves the liquid retention ability of the electrolyte, reduces the ion transport resistance, reduces the problem of the electrolyte being extruded at the corners, and avoids lithium-ion corners, ensuring the circulation and bonding performance of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of coating lithium ion battery diaphragms, and in particular to a composite diaphragm and a preparation method and application thereof. Background Art
[0002] In recent years, fossil fuels are increasingly scarce, environmental and ecological problems are becoming more serious, and countries are more and more urgent in their pursuit of clean energy. Lithium-ion batteries have the advantages of high energy density, good rate performance, low self-discharge rate, no memory effect, and green environmental protection, and are widely used in 3C digital products and electric vehicles. As an important component of lithium-ion batteries, the diaphragm plays an important role in conducting ions, isolating positive and negative electrodes, and preventing short circuits.
[0003] PVDF oil-based diaphragms are favored in high-rate soft-pack batteries due to their good adhesion and high porosity. However, the pore size of traditional oil-based diaphragms is small, and their ability to retain electrolyte is limited, which cannot meet the high demand for electrolyte at high rates. In addition, since traditional oil-based diaphragms are not compressible, in the later stages of the cycle, they often cause corner lithium precipitation due to the expansion of the pole pieces and the extrusion of electrolyte at the corners. Third, most of the pores in traditional oil-based diaphragms are not through-holes, and the resistance to lithium ion transmission is large, which poses a problem for further increasing the rate of the battery cells.
[0004] Therefore, it is necessary to find a composite diaphragm with high adhesion, large through-pores, compressibility and high liquid storage capacity to solve the above problems. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a composite diaphragm having high adhesion and compressibility and a large through-hole structure.
[0006] The invention also provides a method for preparing the composite oil-based diaphragm.
[0007] The present invention also provides a lithium ion battery.
[0008] According to an embodiment of the first aspect of the present invention, a composite diaphragm is provided, wherein the oil-based diaphragm comprises a base film and a composite coating layer coated on one side or both sides of the base film.
[0009] The slurry of the composite coating includes organic polymer A and organic polymer B;
[0010] Wherein, the mass ratio of the organic polymer A to the organic polymer B is (2-4): (6-8);
[0011] The particle size distribution width of the organic polymer B = (D90-D10) / D50 is 1-3.
[0012] The composite diaphragm according to the embodiment of the present invention has at least the following beneficial effects:
[0013] The composite oil-based diaphragm of the present invention comprises a base film and a composite coating coated on one or both sides of the base film, wherein the composite coating is added to the slurry in proportion and includes an infrared absorption peak with a frequency of 2000 to 300 cm -1 The organic polymer A with a characteristic XRD diffraction peak between 2θ=10 and 40°, a crystallinity of 15% to 35%, a Young's modulus of 500 to 2000 MPa, and a molecular weight of 30W-100W can improve the bonding ability with the pole piece, avoid the interface problems that are prone to occur after the pole piece cyclic expansion, and ensure the later cycle performance; the present invention also defines the mass ratio of organic polymer A and organic polymer B, the content of organic polymer B is greater than the content of organic polymer A, if the content of organic matter B is too little, the Gap ability of the coating is small, there is no improvement on the corner, and lithium precipitation at the corner is serious; if the content of organic matter B is too much, the adhesion is weaker, and OH lithium precipitation is serious.
[0014] The present invention also defines the particle size distribution width = (D90-D10) / D50 as 1-3, the D50 particle size as 5-15 μm, and the organic polymer B is a secondary agglomerate of primary particles or a large primary particle, so that the coating has compressibility, which can greatly reduce the proportion of electrolyte squeezed out at the corners due to the expansion of the cyclic electrode, and reduce the risk of lithium deposition at the corners.
[0015] The coating in the composite oil-based diaphragm of the present invention has both large through holes and Gap capabilities (compressibility), which greatly improves the electrolyte retention capacity and reduces the ion transmission resistance, providing a better diaphragm solution for high-rate batteries; the combination of the large through holes and Gap of the coating can not only reduce the problem of electrolyte being squeezed out at the corners due to the expansion of the pole pieces, but also reduce the lithium ion transmission resistance at the corners, so that lithium ions will not accumulate and precipitate at the corners, providing a good solution for lithium precipitation at the corners; with high-adhesion organic polymers, it is ensured that the circulation process will not cause circulation diving problems due to poor interfaces.
[0016] According to some embodiments of the present invention, the mass ratio of the organic polymer A to the organic polymer B is (2-4):(6-8).
[0017] Preferably, the mass ratio of the organic polymer A to the organic polymer B is 3:7.
[0018] According to some embodiments of the present invention, the slurry of the composite coating comprises, by mass percentage:
[0019] Organic polymer A 20%-40%;
[0020] Organic polymer B 60%-80%.
[0021] According to some embodiments of the present invention, the organic polymer A and / or the organic polymer B satisfies at least one of the following:
[0022] a. The molecular weight of the organic polymer A is 30w to 100w;
[0023] b. The XRD diffraction characteristic peak of the organic polymer A is 2θ=10~40°;
[0024] c. The Young's modulus of the organic polymer A is 500 to 2000 MPa;
[0025] d. D10 of the organic polymer B is 1.0 to 3.0 μm;
[0026] e. D90 of the organic polymer B is 8.0 to 20.0 μm;
[0027] f. The D50 particle size of the organic polymer B is 4.8 to 15.0 μm.
[0028] According to some embodiments of the present invention, the molecular weight of the organic polymer A is 30w-100w.
[0029] Preferably, the molecular weight of the organic polymer A is 60w-80w.
[0030] According to some embodiments of the present invention, the XRD diffraction characteristic peak of the organic polymer A is 2θ=10-40°.
[0031] Preferably, the XRD diffraction characteristic peak of the organic polymer A is 2θ=15-30°.
[0032] Within this range, the polymer has good crystallinity (crystallinity 15%-35%), ensuring minimal swelling of the separator in the electrolyte.
[0033] According to some embodiments of the present invention, the Young's modulus of the organic polymer A is 500-2000 MPa.
[0034] Preferably, the Young's modulus of the organic polymer A is 600-1500 MPa.
[0035] Within this range, the organic polymer A has good adhesion to the electrode, ensuring a good circulation interface.
[0036] According to some embodiments of the present invention, the organic polymer A includes a copolymer of at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene and trifluoroethylene.
[0037] According to some embodiments of the present invention, the particle size distribution width of the organic polymer B = (D90-D10) / D50 is 1-3.
[0038] Preferably, the particle size distribution width of the organic polymer B = (D90-D10) / D50 is 1.5-2.
[0039] Among them, the particle size distribution width is too wide, the particle size is not concentrated, the effective particles forming the Gap are reduced, and the Gap capacity is reduced.
[0040] According to some embodiments of the present invention, D10 of the organic polymer B is 1.0-3.0 μm.
[0041] Preferably, D10 of the organic polymer B is 2.0-3.5 μm.
[0042] According to some embodiments of the present invention, D90 of the organic polymer B is 8.0-20.0 μm.
[0043] Preferably, D90 of the organic polymer B is 10.0 to 16.0 μm.
[0044] According to some embodiments of the present invention, the D50 particle size of the organic polymer B is 4.8-15.0 μm.
[0045] Preferably, the D50 particle size of the organic polymer B is 5.0-12 μm.
[0046] If D50 is too large, the coating thickness will be too thick; if it is too small, the Gap capacity will be insufficient or even no Gap will exist.
[0047] According to some embodiments of the present invention, the organic polymer B includes a copolymer of at least one of polyamide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether and acrylate.
[0048] According to some embodiments of the present invention, the slurry of the composite membrane further includes an inorganic substance C.
[0049] According to some embodiments of the present invention, the inorganic substance C includes at least one of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide and boehmite.
[0050] According to some embodiments of the present invention, the specific surface area of the inorganic substance C is 10-30 m 2 / g.
[0051] Preferably, the specific surface area of the inorganic substance C is 10 to 25 m 2 / g.
[0052] Among them, the inorganic material has a too small specific surface area, a large particle size, and a thick thickness, which leads to a decrease in Gap capacity.
[0053] According to some embodiments of the present invention, the slurry of the composite membrane further includes an additive.
[0054] According to some embodiments of the present invention, the additive includes at least one of dioctyl phthalate (DOP), dibutyl phthalate (DBP), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), lithium chloride (LiCl), acetic acid, isopropyl alcohol and glycerol.
[0055] Among them, the proportion of the additives will directly affect the pore structure (size, curvature, etc.), thereby affecting the resistance of lithium ion transmission and limiting the further improvement of the battery cell rate.
[0056] According to some embodiments of the present invention, the slurry solid content of the composite coating is 5% to 20%.
[0057] According to some embodiments of the present invention, the total thickness of the composite coating is 4-6 μm.
[0058] According to some embodiments of the present invention, the slurry of the composite coating further includes an auxiliary additive.
[0059] According to some embodiments of the present invention, the auxiliary auxiliary agent includes at least one of dimethylacetamide (DMAC), dichloroethane, dimethylformamide (DMF), trichloroethane, chloroform, ethyl acetate, sulfolane, dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), chloroform, dichloromethane and acetone.
[0060] According to some embodiments of the present invention, the base film is a PE / PP or PE / PP / PE composite isolation film.
[0061] According to some embodiments of the present invention, the base film has a thickness of 3 to 20 μm.
[0062] According to some embodiments of the present invention, the porosity of the base film is 20-50%.
[0063] According to some embodiments of the present invention, the air permeability of the base film is 30 to 400 sec / 100cc.
[0064] According to an embodiment of the second aspect of the present invention, a method for preparing the composite oil-based diaphragm is provided, the method comprising the following steps:
[0065] S1, stirring and dispersing the inorganic substance C in the auxiliary agent to obtain an inorganic substance C dispersion;
[0066] S2, stirring and dissolving the organic polymer A in the auxiliary agent, adding the organic polymer B and stirring and dispersing to obtain a polymer AB dispersion;
[0067] S3, adding the inorganic substance C dispersion in step S1 to the polymer AB dispersion in step S2, stirring and adding additives to obtain a composite coating slurry;
[0068] S4, coating the composite coating slurry in step S3 on the surface of the base film to obtain the composite oil-based diaphragm.
[0069] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0070] The order of adding materials in the preparation method of the present invention directly affects the dissolution or dispersion state of the components, thereby affecting the microstructure of the diaphragm, resulting in changes in the adhesion and pore structure of the coating.
[0071] According to some embodiments of the present invention, in steps S1, S2 and S3, the rotation speed of the stirring step includes revolution of 10 to 40 rpm / min and rotation of 200 to 2000 rpm / min.
[0072] Preferably, in steps S1, S2 and S3, the rotation speed of the stirring step includes revolution of 20 to 30 rpm / min and rotation of 800 to 1500 rpm / min.
[0073] According to some embodiments of the present invention, in steps S1 and S3, the temperature of the stirring step is 20-25°C.
[0074] According to some embodiments of the present invention, in step S2, the temperature of the stirring step is 40-60°C.
[0075] According to an embodiment of the third aspect of the present invention, there is provided a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and the composite separator, wherein the composite separator is located between the positive electrode sheet and the negative electrode sheet.
[0076] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0077] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0078] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0079] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0080] Embodiments of the present invention are described in detail below, examples of the embodiments, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The following is exemplary by reference to the embodiments, which are only used to explain the present invention and cannot be understood as limiting the present invention.
[0081] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0082] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0083] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0084] Polyvinylidene fluoride LBG: Arkema Group;
[0085] Acrylate copolymer CFL: CAS number is 25133-97-5, from Shenzhen Delixin Material Technology Co., Ltd.;
[0086] Alumina: CAS number is 1344-28-1, Zhejiang Jidun New Material Technology Co., Ltd.
[0087] Example 1
[0088] This embodiment provides a composite diaphragm, and the preparation method thereof comprises the following steps:
[0089] 1) Using dimethylacetamide (DMAC) at a revolution of 30 rpm / min and a rotation of 1500 rpm / min, a surface area of 25 m 2 / g of aluminum oxide was stirred and dispersed uniformly for 30 minutes to obtain an inorganic dispersion with a solid content of 30%;
[0090] 2) According to the dry weight percentage, the organic polymer A polyvinylidene fluoride with a molecular weight of 70W, an XRD diffraction characteristic peak of 20-25°, a Young's modulus of 500-2000MPa, and a dry weight percentage of 39.9% is first stirred and dissolved at 45°C, a revolution of 30rpm / min, and a rotation of 1500rpm / min for 90min, and then the organic polymer B acrylic ester copolymer with a dry weight percentage of 70% corresponding to D50=5μm and a particle size distribution width (D90-D10) / D50 of 3 is added, and the mixture is stirred and dispersed under the same stirring conditions at room temperature for 60min to obtain a polymer AB dispersion with a solid content of 50%;
[0091] 3) adding the inorganic dispersion of step 1) to the polymer AB dispersion, mixing at a ratio of 1:1, stirring and dispersing for 30 minutes at a revolution of 30 rpm / min and a rotation of 1500 rpm / min, adding an additive (DOP:DBP=2:1) with a dry weight ratio of 0.1%, and diluting with dimethylacetamide (DMAC) to a solid content of 10%, while adjusting the stirring revolution to 15 rpm / min and the rotation to 200 rpm / min, and dispersing for 30 minutes to obtain a composite coating slurry;
[0092] 4) The composite coating slurry was coated on both sides of the 7 μm (porosity 38%) base film in a micro-gravure manner, with a coating thickness of 1 μm on one side to obtain a composite-based lithium-ion battery separator.
[0093] Application Examples
[0094] This application example provides a method for preparing a lithium-ion battery, and the specific method includes the following steps:
[0095] 1) Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are mixed in a mass ratio of 97:1.5:1.5, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 8μm, and the aluminum foil is dried at 125°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 125°C for 2h to obtain a positive electrode with a specification of 65mm×860mm.
[0096] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the binder styrene butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 98:1:1, add deionized water, and stir evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 60wt%. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 6μm, and the copper foil is dried at 120°C to obtain a negative electrode coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode coated with a negative electrode material layer on both sides. Then, after cold pressing, cutting and slitting, it is dried under vacuum conditions at 120°C for 2h to obtain a negative electrode with a specification of 69mm×868mm.
[0097] 3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, EC, PC and DMC were mixed in a mass ratio of 3:2:4 to obtain an organic solvent, and then lithium hexafluorophosphate was added to the organic solvent to obtain an electrolyte, wherein the concentration of the lithium salt was 1 mol / L.
[0098] 4) Assembly of lithium-ion battery: stack the positive electrode, separator and negative electrode prepared above in order, place the separator between the positive electrode and the negative electrode to play a role of isolation, and wind to obtain an electrode assembly. Place the electrode assembly in an aluminum-plastic film packaging bag, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, degassing, trimming and other processes.
[0099] The battery separators of the embodiments and comparative examples were further assembled into lithium-ion batteries using the above method, and the battery performance was further tested.
[0100] Examples 2 to 9 and Comparative Examples 1 to 5 were prepared according to the slurry parameters shown in Table 1, and the preparation method was the same as that of Example 1.
[0101] Table 1 Parameters of Examples 2 to 9 and Comparative Examples 1 to 5
[0102]
[0103]
[0104]
[0105] Test Case
[0106] Performance tests were performed on Examples 2 to 9 and Comparative Examples 1 to 5. The performance test method included:
[0107] Coating thickness: Finished diaphragm thickness minus base film thickness. Thickness test is done directly with a Mahr thickness gauge.
[0108] Coating air permeability: the time required for 100cc of finished membrane to pass through a certain area - the time required for 100cc of base membrane to pass through a certain area;
[0109] Adhesion strength: The diaphragm and the electrode are soaked in electrolyte for 24 hours respectively, and then the surface electrolyte is wiped dry, and then the peeling force is measured by hot pressing at 85℃*1MPa*60min, and the adhesion per unit width is calculated;
[0110] Gap value: first measure the thickness D1 of the 8-layer diaphragm, then measure the thickness D2 of the 8-layer diaphragm after hot pressing (85℃*1Mpa*1h), and the Gap value is D1-D2;
[0111] Thickness after hot pressing: refers to the thickness of the coating after hot pressing. This thickness is a calculated value, which is equal to the total thickness minus the thickness of the coating after hot pressing (the Gap value here is the thickness of 8 layers, so a single layer needs to be divided by 8);
[0112] Cycle interface: Place the lithium-ion battery in a 25℃ environment, let it stand for 30 minutes, charge it to 4.50V at 3.5C constant current, then charge it to 0.05C at 4.50V constant voltage, let it stand for 5 minutes, and discharge it to 3.0V at 0.7C constant current. This is one cls. After cycling to 300cls, disassemble the battery cell interface and observe the lithium deposition on the negative electrode.
[0113] Table 2 Performance test results of Examples 2 to 9 and Comparative Examples 2 to 6
[0114]
[0115] According to the results in Table 2, we can see that:
[0116] 1) Comparative Example 1 Compared with the embodiment, the addition of organic polymer B can make the coating have Gap ability (compressibility), which can greatly reduce the proportion of electrolyte squeezed out at the corners due to the expansion of the cycle electrode, and reduce the risk of lithium deposition at the corners;
[0117] 2) Compared with Example 2, Example 1 has a larger (D90-D10) / D50 and a smaller D10, indicating that the particle size of the organic polymer B is more dispersed, there are more large particles and small particles, the thickness fluctuates greatly, and there are more large particles. The thickness is slightly thicker after hot pressing. If this continues, the battery cell has a risk of being slightly too thick;
[0118] 3) In Example 3, (D90-D10) / D50 is smaller than in Example 2, indicating that the particle size of the organic polymer B is concentrated, the thickness is slightly thick after hot pressing, and the battery cell has a slight risk of being too thick. In addition, the more concentrated the particle size of the polymer B is, the higher the cost will be.
[0119] 4) In Example 4, compared with Example 2, the molecular weight of the organic polymer A is small, the Young's modulus is large, and the crystallinity 2θ is high, which means that the material is harder, the adhesion is lower, and slight lithium precipitation occurs at the OH position;
[0120] 5) Example 5 Compared with Example 2, the molecular weight of organic polymer A is large, the crystallinity 2θ is low, the Young's modulus is low, the adhesion of the material is too strong, the electrolyte diffusion is problematic, and there are slight black spots on the main body interface. In addition, the molecular weight of organic polymer A is large, the porosity is poor, the air permeability is slightly high, and the lithium ion transmission resistance is large, which may also cause black spots on the main body;
[0121] 6) In Example 6, relative to Example 2, the specific surface area of the inorganic material is small, indicating that the inorganic material has a large particle size, and the adhesion with the electrode is significantly affected, resulting in slight lithium deposition of OH. In addition, its thickness is relatively large, and the Gap capacity is relatively small (the inorganic material is incompressible), resulting in slight lithium deposition at the corners, and there is a greater risk of over-thickness;
[0122] 7) Compared with Example 2, Example 7 has a high content of organic matter B, weak adhesion, and a risk of lithium deposition in OH, and there is a risk of excessive thickness;
[0123] 8) Compared with Example 2, Example 8 has less organic matter B content, smaller coating gap capacity, smaller corner improvement capacity, and smaller lithium deposition risk;
[0124] 9) In Comparative Example 2, (D90-D10) / D50 is larger than in Example 2, and D90 is very large, which is higher than the specification, indicating that the particle size of organic polymer B is more dispersed, there are more large-size particles, the thickness is thick, the coating thickness fluctuates greatly, the thickness is slightly thicker after hot pressing, and the battery cell is over-thick. In Comparative Example 2, due to the large number of large particles, the adhesion between the diaphragm and the electrode is weakened, and severe lithium precipitation occurs at the OH;
[0125] 10) In Comparative Example 6, relative to Example 2, (D90-D10) / D50 is smaller and lower than the specification, indicating that the particle size of organic polymer B is more concentrated, the Gap value and adhesion are equivalent, the interface is good, and the battery core is slightly thicker, but it is difficult for the supplier of organic polymer B to prepare samples and the cost is higher;
[0126] 11) Comparative Example 3 Compared with Example 2, the molecular weight of the organic polymer A is small, the crystallinity 2θ is low, the Young's modulus is low, the adhesion is weak, and the OH lithium precipitation is serious;
[0127] 12) Comparative Example 4 Compared with Example 2, the content of organic matter B is higher, the bonding force is weaker, and OH lithium precipitation is serious;
[0128] 13) In Comparative Example 5, compared with Example 2, the content of organic matter B is less, the Gap capacity of the coating is small, there is no improvement on the corners, and lithium deposition on the corners is serious.
[0129] In summary, Example 3 of the present invention achieves the best performance balance through combined optimization. The present invention adjusts the molecular weight, particle size and distribution width of organic polymers A and B, adds a specific proportion of organic polymers A and B, and combines optimized feeding process and additive ratio to achieve a combination of large through holes and Gap capabilities, significantly improves the liquid retention capacity of the electrolyte and reduces the ion transmission resistance, ensures the cycle performance, achieves a comprehensive balance of adhesion performance, Gap capability and air permeability, and meets the needs of high-performance diaphragms.
[0130] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base film and a composite coating coated on one or both sides of the base film; The slurry of the composite coating includes organic polymer A and organic polymer B; Wherein, the mass ratio of the organic polymer A to the organic polymer B is (2-4): (6-8); The particle size distribution width of the organic polymer B = (D90-D10) / D50 is 1-3.
2. The composite diaphragm according to claim 1, characterized in that: The organic polymer A and / or organic polymer B satisfies at least one of the following: a. The molecular weight of the organic polymer A is 30w to 100w; b. The XRD diffraction characteristic peak of the organic polymer A is 2θ=10~40°; c. The Young's modulus of the organic polymer A is 500 to 2000 MPa; d. D10 of the organic polymer B is 1.0 to 3.0 μm; e. D90 of the organic polymer B is 8.0 to 20.0 μm; f. The D50 particle size of the organic polymer B is 4.8 to 15.0 μm.
3. The composite diaphragm according to claim 1, characterized in that: The organic polymer A includes a copolymer of at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene and trifluoroethylene; preferably, the organic polymer B includes a copolymer of at least one of polyamide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether and acrylate.
4. The composite diaphragm according to claim 1, characterized in that: The slurry of the composite coating further includes an inorganic substance C; preferably, the inorganic substance C includes at least one of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide and boehmite.
5. The composite diaphragm according to claim 4, characterized in that: The specific surface area of the inorganic substance C is 10-30m 2 / g.
6. The composite diaphragm according to claim 1, characterized in that: The solid content of the composite coating is 5% to 20%; preferably, the total thickness of the composite coating is 4 to 6 μm.
7. The composite diaphragm according to claim 1, characterized in that: The base film is a PE / PP or PE / PP / PE composite isolation film; preferably, the thickness of the base film is 3 to 20 μm; preferably, the porosity of the base film is 20 to 50%; preferably, the air permeability of the base film is 30 to 400 sec / 100 cc.
8. A method for preparing the composite diaphragm according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1, stirring and dispersing the inorganic substance C in the auxiliary agent to obtain an inorganic substance C dispersion; S2, stirring and dissolving the organic polymer A in the auxiliary agent, adding the organic polymer B and stirring and dispersing to obtain a polymer AB dispersion; S3, adding the inorganic substance C dispersion in step S1 to the polymer AB dispersion in step S2, stirring and adding additives to obtain a composite coating slurry; S4, coating the composite coating slurry in step S3 on the surface of the base film to obtain the composite diaphragm.
9. The preparation method according to claim 8, characterized in that: In steps S1, S2 and S3, the rotation speed of the stirring step includes revolution of 10 to 40 rpm / min and rotation of 200 to 2000 rpm / min; preferably, in steps S1, S2 and S3, the time of the stirring step is 30 to 90 min; preferably, in steps S1 and S3, the temperature of the stirring step is 20 to 25°C; preferably, in step S2, the temperature of the stirring step is 40 to 60°C.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and the composite separator according to any one of claims 1 to 8, wherein the composite separator is located between the positive electrode sheet and the negative electrode sheet.
Citation Information
Cited By
Diaphragm, preparation method thereof and secondary battery
CN120221924A
Diaphragm and battery cell, electrochemical device and electronic equipment comprising same
CN121149587A